The 5P funnel framework: an instructional design for enhancing teachers’ AI competency - Li, Chanyi; Mohamed Mokhtar, Marzni (Faculty of Educational Studies, Universiti Putra Malaysia, 2024)
The strategic research of moral education plays an important role in the field of education. Exploring the effectiveness of moral education is a major topic for improving and promoting educational strategies. This study examines the effectiveness of moral education through focus groups. Through the results of this study, it is found that the strategy of enhancing life reality and experiential learning and using teachers as facilitators to conduct moral education is more effective, it is effective for students to participate in moral education in life while seeking strategic education courses. This study may provide a theoretical basis for this field and may help policy designers in curriculum design.